The Wheat Bax Inhibitor-1 Protein Interacts with an Aquaporin TaPIP1 and Enhances Disease Resistance in Arabidopsis - Lu, Pan-Pan; Yu, Tai-Fei; Zheng, Wei-Jun; Chen, Ming; Zhou, Yong-Bin; Chen, Jun; Ma, You-Zhi; Xi, Ya-Jun; Xu, Zhao-Shi (Frontiers in Plant Science, 2018)
Bax inhibitor-1 (BI-1) is an endoplasmic reticulum (ER)-resident cell death suppressor evolutionarily conserved in eukaryotes. The ability of BI-1 to inhibit the biotic and abiotic stresses have been well studied in Arabidopsis, while the functions of wheat BI-1 are largely unknown. In this study, the wheat BI-1 gene TaBI-1.1 was isolated by an RNA-seq analysis of Fusarium graminearum (Fg)-treated wheat. TaBI-1.1 expression was induced by a salicylic acid (SA) treatment and down-regulated by an abscisic acid (ABA) treatment. Based on β-glucuronidase (GUS) staining, TaBI-1.1 was expressed in mature leaves and roots but not in the hypocotyl or young leaves. Constitutive expression of TaBI-1.1 in Arabidopsis enhanced its resistance to Pseudomonas syringae pv. Tomato (Pst) DC3000 infection and induced SA-related gene expression. Additionally, TaBI-1.1 transgenic Arabidopsis exhibited an alleviation of damage caused by high concentrations of SA and decreased the sensitivity to ABA. Consistent with the phenotype, the RNA-seq analysis of 35S::TaBI-1.1 and Col-0 plants showed that TaBI-1.1 was involved in biotic stresses. These results suggested that TaBI-1.1 positively regulates SA signals and plays important roles in the response to biotic stresses. In addition, TaBI-1.1 interacted with the aquaporin TaPIP1, and both them were localized to ER membrane. Furthermore, we demonstrated that TaPIP1 was up-regulated by SA treatment and TaPIP1 transgenic Arabidopsis enhanced the resistance to Pst DC3000 infection. Thus, the interaction between TaBI-1.1 and TaPIP1 on the ER membrane probably occurs in response to SA signals and defense response.